“My brain doesn't communicate with my hands”: navigating negotiated interaction in Swedish and Indonesian supervision - Nangimah, Musrifatun (Frontiers in Education, 2024)
The importance of supervisory interaction facilitated by dialogic feedback is known to create a shared understanding between supervisors and students. However, previous studies of supervisory interaction mainly focus on exploring feedback provision as an input for specific improvement rather than as a process of interaction regardless of its discursivity. Informed by learning community theory, this study explores how thesis supervision in English as an Additional Language contexts is negotiated to identify the supervisory interaction patterns and strategies. Methodologically, this study applied a qualitative case study by involving 6 supervisory dyads (6 supervisors and 15 students) in English-medium study programs. Thematic analysis was used to analyze 18 video-recorded supervision sessions from the beginning, the middle, and the end of the supervision process. The findings illuminate the negotiated interaction patterns and strategies in supervisory meetings that can be organized into three themes: (1) managing correction, (2) managing scaffolding, and (3) managing students’ emotional expressions. The supervisory interaction patterns tend to take the form of a common institutional talk due to the students’ desire for confirmation and suggestions. Prompting strategies through exploratory questions can scaffold students’ development of argumentative skills although students’ deviant responses frequently lead to supervisors’ further explanation. The theoretical analysis underscores that learning community theory emphasizes the development of student’s academic literacy and argumentative proficiency through dialogic inquiry. Yet, effective engagement in such inquiry necessitates prerequisite academic literacy and rhetorical competencies. In conclusion, this study highlights the need for developing student’s academic literacy, research literacy, and communication skills to achieve an effective inquiry dialogue in thesis supervision.